2021
DOI: 10.1111/jsr.13368
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 lockdown and poor sleep quality: Not the whole story

Abstract: A growing body of evidence consistently describes the side‐effects of coronavirus disease 2019 lockdown on mental health and sleep quality. We conducted a longitudinal web‐based survey of 217 Italian participants at two time points: lockdown and subsequent follow‐up. To thoroughly investigate lockdown‐related changes in sleep quality, we first evaluated variations in overall sleep quality assessed by the Pittsburgh Sleep Quality Index. We then examined sleep changes in specific components of sleep quality. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
61
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 25 publications
15
61
0
2
Order By: Relevance
“…This finding is only apparently in conflict with the activation/arousal-retrieval model. In fact, the phenomenon of sleep extension during lockdown has been described by Bottary et al (2020) highlighting that even if people spontaneously prolonged their sleep duration, the rest could be featured by poor quality and fragmentation, and confirmed by recent data (Alfonsi et al, 2021).…”
Section: Discussionsupporting
confidence: 56%
“…This finding is only apparently in conflict with the activation/arousal-retrieval model. In fact, the phenomenon of sleep extension during lockdown has been described by Bottary et al (2020) highlighting that even if people spontaneously prolonged their sleep duration, the rest could be featured by poor quality and fragmentation, and confirmed by recent data (Alfonsi et al, 2021).…”
Section: Discussionsupporting
confidence: 56%
“…Kocevska and colleagues ( 2020 ) found no uniform effect on sleep, with some individuals experiencing improvements as compared to pre‐pandemic times, whereas others noted worse sleep that was often associated with pandemic anxiety. This was also seen in Italy, France and Spain, where worse sleep quality was more frequently reported than improved sleep quality (Alfonsi et al, 2021 ; Dal Santo et al, 2021 ; Ruby, 2021 ).…”
Section: Introductionmentioning
confidence: 80%
“…Blue‐light‐emitting devices are known to suppress melatonin production and thus disturb sleep (Cajochen et al, 2011 ). These factors may have contributed to the increase in sleep medication use seen during confinement by Alfonsi and colleagues ( 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐sectional web‐surveys carried out among Italian people revealed that more than half of participants reported poor sleep quality (Alfonsi et al, 2021 ; Casagrande et al, 2020 ; Franceschini et al, 2020 ), and sleep timing changes were found in parallel with sleep difficulties (Cellini et al, 2020 ). In addition, increased sleep disturbances and hypnotic medications were observed (Jahrami et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%